2020
DOI: 10.1007/s42452-020-03872-y
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic analysis of a working posture in steel industry in Egypt using digital human modeling

Abstract: This study presents solutions for improving a bending awkward posture in steel industry in Egypt using digital Human Modeling (DHM). The information is gathered by interviewing the workers, working postures are recorded via a video camera while the worker is performing his usual work. The postures are analyzed using DHM software. Porter comfort analysis and Rapid Upper Limb Assessment are applied for postures analysis. The analysis shows high levels of discomfort in neck, trunk, leg and forearm. These discomfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(21 reference statements)
0
5
0
1
Order By: Relevance
“…In a step prior to this research, a preliminary ergonomic assessment of working conditions was applied to analyze the existing relationships between the demands of diseases in the musculoskeletal system in mining maintenance professionals and the ergonomic adaptation needs of the studied equipment. It was assessed the factors that could affect, directly or indirectly, the emergence of musculoskeletal diseases (Mohammed et al, 2020). Following a structured protocol for data collection (Yin, 2010;Budiyanto et al, 2019), the maintenance activities of the three equipment studied were first observed and recorded.…”
Section: Advanced Technologies In Traditional Industrymentioning
confidence: 99%
See 2 more Smart Citations
“…In a step prior to this research, a preliminary ergonomic assessment of working conditions was applied to analyze the existing relationships between the demands of diseases in the musculoskeletal system in mining maintenance professionals and the ergonomic adaptation needs of the studied equipment. It was assessed the factors that could affect, directly or indirectly, the emergence of musculoskeletal diseases (Mohammed et al, 2020). Following a structured protocol for data collection (Yin, 2010;Budiyanto et al, 2019), the maintenance activities of the three equipment studied were first observed and recorded.…”
Section: Advanced Technologies In Traditional Industrymentioning
confidence: 99%
“…The lack of an ergonomic perspective in the design of the equipment, without the participation of “conception actors” (Daniellou, 2012), provides harmful working conditions to the health of maintenance professionals. In this way, maintenance professionals are exposed to noise, vibrations, heat and muscle fatigue that generate serious ergonomic problems (Mohammed et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selanjutnya penelitian terkait analisis ergonomi postur kerja di industri baja di Mesir dengan menggunakan digital human modeling yang sesuai dengan pada industri baja diraih bahwa skor RULA pekerja dengan munggunakan simulasi bernilai 6-7 atau pekerjaan tersebut memiliki risiko sangat tinggi untuk terjadinya masalah musloskeletal disorders [7]. Penelitian selanjutnya tentang postur kerja, kondisi kerja dan musculoskeletal disoreders pada pekerja pertanian di Iran ditemukan hasilnya bahwa risiko terjadinya musculoskeletal disorders bernilai 5-7 atau risiko tinggi hingga risiko sangat tinggi dan memerlukan perubahan secepatnya [8].…”
Section: Pendahuluanunclassified
“…As a solution, a time study was carried out with a stopwatch, the application of the RULA and REBA tools, finally, the DOP was used to identify the operations and times in seconds that companies require. Downtime reduced by 41%, only required 50% of available labor and increased productivity by 40% [21].…”
Section: B Ergonomicsmentioning
confidence: 99%